Variability of the drug response to nonsteroidal anti-inflammatory drugs according to cyclooxygenase-2 genetic polymorphism - Lee SJ; Park MK; Shin DS; Chun MH (Dove Medical Press, 2017)
Sook Joung Lee,1,* Min Kyu Park,2,* Dong-Seong Shin,3 Min Ho Chun4 1Department of Physical Medicine and Rehabilitation, Dong-A University College of Medicine, Dong-A University Hospital, 2Department of Pharmacology and Clinical Pharmacology, Dong-A University College of Medicine, Dong-A University Hospital, Busan, 3Clinical Trials Center, Gachon University Gil Medical Center, Incheon, 4Department of Rehabilitation Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of Korea *These authors contributed equally to this work Purpose: Cyclooxygenase (COX) is the main pharmacodynamic target of nonsteroidal anti-inflammatory drugs (NSAIDs). We investigated the inhibitory effects on COX-2 after NSAIDs administration using a lipopolysaccharide (LPS)-derived COX-2 induction model in whole blood, according to the genotypes of COX-2 single-nucleotide polymorphisms (SNPs). Patients and methods: Seven genotypes of COX-2 SNPs were selected from public databases and analyzed in 324 healthy subjects. Two genotypes showing a high percentage of variability were selected. A clinical trial examining pharmacodynamics according to the genotype of two SNPs (rs5275 and rs689466) was conducted. Twenty subjects were administered a single oral dose of 200 mg of celecoxib, and pharmacokinetic and pharmacodynamic analyses were performed. Results: In the analysis of the pharmacokinetic parameters, significant differences in drug exposure were not investigated for each SNP genotype. The pharmacodynamic analysis revealed that the maximum effect of COX-2 inhibition was achieved at 2.0 hours for all genotypes of COX-2 SNPs after a single oral administration of 200 mg celecoxib. The inhibitory effects according to the genotype of COX-2 SNPs were investigated, and the area under the effect curve of the rs689466 GG genotype was significantly lower than that for the AA or AG genotype. Conclusion: Our results demonstrated that inhibitory effects of celecoxib on COX-2 induction were different according to the genotype of COX-2 SNPs. In the present study, rs689466 is responsible for the variability of the response to celecoxib, suggesting that a subject with the GG genotype of rs689466 would be more responsive to celecoxib in terms of COX-2 inhibition. Keywords: nonsteroidal anti-inflammatory agent, cyclooxygenase-2, single-nucleotide polymorphism, drug response, pharmacodynamics, clinical trial